2022
DOI: 10.1038/s41467-022-34043-9
|View full text |Cite
|
Sign up to set email alerts
|

Observation of gapped Dirac cones in a two-dimensional Su-Schrieffer-Heeger lattice

Abstract: The Su-Schrieffer-Heeger (SSH) model in a two-dimensional rectangular lattice features gapless or gapped Dirac cones with topological edge states along specific peripheries. While such a simple model has been recently realized in photonic/acoustic lattices and electric circuits, its material realization in condensed matter systems is still lacking. Here, we study the atomic and electronic structure of a rectangular Si lattice on Ag(001) by angle-resolved photoemission spectroscopy and theoretical calculations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Guo-min He, on the basis of DFT calculations, showed that the dimer model for the (3 × 3) reconstruction was unstable, and proposed alternative models. 125 However, in a combined ARPES-DFT study, Geng et al 126 recently proposed a model composed of Si dimers, analogous to that proposed by Léandri et al 34 where the dimers are not tilted and the topmost Ag layer is reconstructed with missing Ag atoms. Guo-min He also proposed models for higher coverage structures, but they are associated with substrate reconstructions different than the (7 × 4) experimentally observed.…”
Section: Substratementioning
confidence: 98%
“…Guo-min He, on the basis of DFT calculations, showed that the dimer model for the (3 × 3) reconstruction was unstable, and proposed alternative models. 125 However, in a combined ARPES-DFT study, Geng et al 126 recently proposed a model composed of Si dimers, analogous to that proposed by Léandri et al 34 where the dimers are not tilted and the topmost Ag layer is reconstructed with missing Ag atoms. Guo-min He also proposed models for higher coverage structures, but they are associated with substrate reconstructions different than the (7 × 4) experimentally observed.…”
Section: Substratementioning
confidence: 98%
“…Although it may seem an intricate endeavor, our ideas are not beyond the scope of the experimental reach. We may mention the experimental results in [35]. They studied the atomic and electronic structure of a rectangular Si lattice on Ag(001) using angle-resolved photoemission spectroscopy and theoretical calculations.…”
Section: IIImentioning
confidence: 99%
“…These materials exhibit unique topological boundary states linked to their nontrivial bulk topology, often attributed to Berry curvature. The two-dimensional (2D) extension of the SSH model has recently garnered significant attention [29][30][31][32][33][34][35], revealing unique properties such as fractional wave polarization and high-order topological states.…”
mentioning
confidence: 99%
“…The physical and chemical properties of common materials are governed by electrons or holes with finite effective masses, i.e., massive fermions [1]. Recently, a series of materials that contain unique particles called Dirac fermions (DFs) have gained considerable scientific attention [1][2][3][4][5][6]. These particles possess unusually small effective masses and unusually high mobilities because of their Fermi velocities.…”
Section: Introductionmentioning
confidence: 99%
“…It has not been examined experimentally how the reversible conversion of massive and massless fermions occurs in conjunction with the formation of a Dirac-cone-type band. Since the discovery of DFs in graphene and related inorganic substances, many studies have focused on stable two-dimensional (2D) compounds with simple chemical formulae and high structural symmetries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Such samples are often more easily available than the organic DF systems and favor clear discussion based on precise theoretical analyses such as first-principles band calculations.…”
Section: Introductionmentioning
confidence: 99%